Intestinal Parasites and the Occurrence of Zoonotic Giardia duodenalis Genotype in Captive Gibbons at Krabokkoo Wildlife Breeding Center, Thailand - Tangtrongsup, Sahatchai; Sripakdee, Duanghatai; Malaivijitnond, Suchinda; Angkuratipakorn, Rungroj; Lappin, Michael (Frontiers in Veterinary Science, 2019)
Intestinal parasitic infections can have an impact on health and growth of wildlife. The current study aims were to determine the prevalence of intestinal parasites and to molecular characterize Giardia duodenalis. and Cryptosporidium spp. in captive gibbons at Krabokkoo Wildlife Breeding Center, Thailand. Fifty-five gibbons, 2 agile- (Hylobates agilis), 38 lar- (Hylobates lar) and 15 pileated gibbons (Hylobates pileatus) were included in this study. Fecal samples were collected individually at Krabokkoo Wildlife Breeding Center, Chachoengsao province, eastern Thailand, in November 2013. Intestinal parasitic infections were examined by zinc sulfate centrifugation flotation and by a commercially available immunofluorescent assay (IFA) for detection of G. duodenalis and Cryptosporidium spp.. Polymerase chain reaction targeting the Giardia glutamate dehydrogenase (gdh), beta- giardin (bg), triose phosphate isomerase (tpi) genes and the Cryptosporidium small subunit-rRNA and heat-shock protein (hsp70) following by DNA sequencing were performed on the IFA positive samples. The overall prevalence of intestinal parasitic infection in gibbons at Krabokkoo Wildlife Breeding Center was 12.7% (95%CI: 5.3-24.5), Strongyloides spp. eggs or larvae were present in all positive samples. Co-infections with G. duodenalis were detected in 1.8% (95%CI: 0.1-9.7) of the samples. Based on the sequencing results of the three genes, the IFA Giardia positive isolate typed as the zoonotic genotype B. Since the data reveals the occurrence of zoonotic Giardia genotype, good hygiene management is suggested to prevent the transmission of this pathogen from gibbon to human, and vice versa.